2012
DOI: 10.1590/s0100-204x2012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Respostas fisiológicas de cultivares de soja à adubação potássica sob diferentes regimes hídricos

Abstract: Resumo -O objetivo deste trabalho foi avaliar a interferência da adubação potássica em parâmetros fisiológicos de duas cultivares de soja, sob diferentes regimes hídricos. O experimento foi realizado em condições de casa de vegetação, em Presidente Prudente, SP. Utilizou-se o delineamento experimental inteiramente casualizado, em arranjo fatorial 2x2x3, com as cultivares BR-16 (tolerante ao estresse hídrico) e Embrapa 48 (suscetível), regimes hídricos com reposição diária de água de 100% (controle) e de 40% da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 23 publications
6
23
0
18
Order By: Relevance
“…Thus, it can be claimed that the mineral fertilization released nutrients satisfactorily, conditioning plants with increased vigor and, consequently, higher growth and gas exchanges. This is confirmed by Catuchi et al (2012), who studied the physiological responses of soybean plants under potassium fertilization and water regimes, and observed an increment in stomatal conductance with the increase in the potassium dose. In addition, the improvement in the availability of nutrients contributes to the gas exchanges and growth of the plants (SEDIYAMA et al, 2014;SANTOS et al, 2014;SÁ et al, 2016).…”
Section: Resultssupporting
confidence: 55%
“…Thus, it can be claimed that the mineral fertilization released nutrients satisfactorily, conditioning plants with increased vigor and, consequently, higher growth and gas exchanges. This is confirmed by Catuchi et al (2012), who studied the physiological responses of soybean plants under potassium fertilization and water regimes, and observed an increment in stomatal conductance with the increase in the potassium dose. In addition, the improvement in the availability of nutrients contributes to the gas exchanges and growth of the plants (SEDIYAMA et al, 2014;SANTOS et al, 2014;SÁ et al, 2016).…”
Section: Resultssupporting
confidence: 55%
“…Brevedan & Egli (2003) applied a severe soil-moisture regime for 13 days to soybean crop, in the pod filling stage, and reported 39% losses of grain yield; however, those authors used only one soybean cultivar (Elgin 87). Catuchi et al (2012) reported greater grain yield losses of soybean subjected to severe levels of soil moisture, for a total of 25 days, from flowering to the beginning of pod filling stage. In the present study, plants were subjected to different water regimes for 13 days (beginning of flowering to the beginning of pod set), which allowed of a sufficient time (55 days) for plants to recover until maturation.…”
Section: Resultsmentioning
confidence: 96%
“…The abiotic stress caused by water deficiency reduces soybean development and yield, caused by diminishing of leaf area (Sincik et al, 2008), and changings on photosynthesis (Fenta et al, 2012), and gas exchange characteristics (Liu et al 2005;Bertolli et al, 2012;Catuchi et al, 2012;Li et al, 2013;Madhu & Hatfield, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The soil moisture was monitored through daily pot weighing and watering, following a previously described procedure (CATUCHI et al, 2012). Soil moisture was maintained at approximately 20% of SWRC, where it has a negative effect on sugarcane growth and physiology but does not cause plant death.…”
Section: How the Components Of Bioenergy And… Como Componentes De La mentioning
confidence: 99%